Mercury Control : for Coal-Derived Gas Streams. - Granite, Evan J. (Wiley, 2014)
This essential handbook and ready reference offers a detailed overview of the existing and currently researched technologies available for the control of mercury in coal-derived gas streams and that are viable for meeting the strict standards set by environmental protection agencies. Written by an internationally acclaimed author team from government agencies, academia and industry, it details US, EU, Asia-Pacific and other international perspectives, regulations and guidelines.